(untitled) (Medical Forum Monthly, 2024)
Objective: To compare complications rate of Titanium elastic nail with External fixator in pediatric femoral diaphyseal fractures. Study Design: Prospective randomized study. Place and Duration of Study: This study was carried out at the Orthopedic Department, Lahore General Hospital/PGMI, Lahore from 01.10.2013 to 01.10.2015. Materials and Methods: Complication rate was compared in two groups of children (20 each) of 5-11 years of age with closed or Gustilo type I open femoral diaphyseal fractures treated with Titanium elastic nailing and external fixator. Results: At final review, 3 patients in External fixator group developed superficial pin tract infection which resolved by oral antibiotics. 2 patients had a LLD (limb length discrepancy) of up to 1cm and 4 patients had mal alignment of 5-10 degree. While only one patient in Titanium elastic nail group developed pain and irritation at medial insertion point and another had mal alignment of 10 degree in AP plane. Overall there was decrease complication rate in Titanium elastic nail group. Conclusion: Titanium elastic nail is a better choice in children of 5-11 years of age with femoral diaphyseal fractures than External fixator.